Determinants of Sustainability Report With Company Size as Moderation - Sari, Maylia Pramono; Prabowo, Gregorius Permana Wahyu Pudji; Ardina, Ayu Martaning Yogi; Raharja, Surya - (Pusat P2M Politeknik Negeri Batam, 2025)
Sustainability reports are important because they relate to the economic, environmental and social impacts caused by a company's activities. This study aims to prove the effect of leverage, liquidity, institutional ownership, managerial ownership on sustainability reports with company size as a moderating variable and profitability as a control variable. This study used purposive sampling, resulting in a sample of 29 Consumer Goods companies listed on the IDX for the 2018-2022 period. The study found that the sustainability reports of Consumer Goods companies are significantly and negatively affected by leverage. Liquidity and managerial ownership do not affect sustainability reporting, and sustainability reporting is positively and significantly affected by institutional ownership. In addition, the relationship between sustainability reports and leverage is supported by the size of the company. However, in consumer goods companies, the relationship between institutional ownership, managerial ownership, and liquidity in sustainability reports is not reinforced by the size of the company.